A Critical Review on Role of Ayurvedic Management of Vandhyatwa (Infertility) (AYUSHDHARA, 2025)
Infertility, an increasingly prevalent global issue, is characterized by the inability to achieve pregnancy after one year of regular, unprotected intercourse. While modern medicine categorizes its causes as ovulatory disorders, tubal defects, uterine anomalies, and unexplained factors, Ayurveda offers a holistic perspective through the concept of Vandhyatwa. This review critically explores the Ayurvedic understanding, classification, pathogenesis, and treatment of Vandhyatwa, emphasizing the imbalance in Artavavaha Srotas, deranged Agni, and vitiation of Doshas- particularly Vata. Classical Ayurvedic texts describe various types of infertility, highlighting both congenital and acquired causes, as well as Doshic and lifestyle-related factors. Ayurvedic management emphasizes root cause treatment through Nidana Parivarjana (removal of causative factors), Shodhana (purification therapies like Vamana, Virechana, Nasya, and Basti), Shamana (pacification), and specialized treatments such as Uttar Basti for uterine and tubal disorders. Additionally, Rasayana and Vajikarana therapies rejuvenate reproductive health, enhance fertility, and reduce stress-induced hormonal imbalances. Yoga and meditation are complementary tools in restoring reproductive balance and mental well-being. The Ayurvedic approach, by addressing physical, psychological, and spiritual aspects, offers a personalized and integrative pathway for managing infertility, especially where modern interventions fall short or are cost-prohibitive. Case studies demonstrate successful conception in patients treated with Ayurvedic protocols, especially in cases labelled as unexplained or resistant to conventional treatments. Thus, Ayurveda presents a comprehensive, effective, and safe alternative in the management of female infertility, especially when integrated with modern diagnostic tools.